Effects of culture medium and light durations on the fungal growth of Bipolaris sorokiniana - Ismail, Maizan; Juraimi, Abdul Shukor; Idris, Abu Seman; Rusli, Mohd Hefni; Raja Omar, Raja Zulkifli; A. Tohiran, Kamil; Husri, Mohd Naqiuddin (Lembaga Minyak Sawit Malaysia, 2023)
Bipolaris sorokiniana has been identified as a potential indigenous fungal plant pathogen to control goosegrass (Eleusine indica) in oil palm plantations. However, for mass production, a suitable medium and an optimum growing environment need to be identified. This study was conducted to determine the suitable culture media and light duration requirements for optimal growth of B. sorokiniana. Four types of culture media: Potato dextrose agar (PDA), corn meal agar (CMA), V8 agar (V8A) and water agar (WA), were evaluated for the B. sorokiniana subculture. Three light durations (0, 12 and 24 hr) were tested for B. sorokiniana growth. The growth diameter and colony-forming units of B. sorokiniana were recorded. When compared to CMA, V8A, and WA media in the same light durations, B. sorokiniana grew at maximum mean growth diameter at 12 hr light duration in PDA (4.56 cm), 24 hr light duration in PDA (4.36 cm) and 0 hr light duration in PDA (4.21 cm). Bipolaris sorokiniana produced more CFU during the 0 light duration than during the 12 hr and 24 hr light durations. Hence, this study shows that B. sorokiniana has the potential for reproduction using PDA culture media without light.